Pembelajaran Fiksi Menggunakan Media Scrapbook Pada Siswa Sekolah Dasar - Johana Kristantie; Kamidjan Kamidjan; Ratih Asmarani (Universitas Islam Madura, 2019)
The problem experienced in this study is the lack of learning resources used by teachers as a medium for learning fiction at the elementary school level. The purpose of this study is to describe the learning process, and student learning outcomes in fiction learning using scrapbook media for students in primary schools. The use of this research method is descriptive qualitative, because it is to provide a picture of actual events regarding the conditions that occur in fiction learning using scrapbook media. The learning process data were analyzed descriptively qualitatively and learning outcomes were analyzed quantitatively. Obtaining learning outcomes from pre-test scores in learning I gained an average of 67 with a percentage of 51.90%, and learning II obtained an average of 64 with a percentage of 46.20%. Meanwhile, the posttest learning outcomes in learning I gained an average of 86 with a percentage of 92.30%, and learning II obtained an average of 88 with a percentage of 92.30%. Based on research data that has been done it can be seen that, scrapbook media can be used as an appropriate source of learning in fiction learning in elementary schools.Keywords: Fiction,Learning, media, scrapbook.Abstrak: Permasalahan yang dialami dalam penelitian ini adalah kurangnya sumber belajar yang digunakan oleh guru sebagai media pada pembelajaran fiksi di jenjang sSekolah dDasar. Tujuan penelitian ini adalah untuk menggambarkan proses pembelajaran, dan hasil belajar siswa pada pembelajaran fiksi menggunakan media scrapbook pada siswa di sSekolah dDasar. Penggunaan metode penelitian ini adalah deskriptif kualitatif, karena untuk memberikan gambaran kejadian secara aktual mengenai kondisi yang terjadi pada pembelajaran fiksi menggunakan media scrapbook. Data proses pembelajaran dianalisis secara deskriptif kualitatif dan hasil belajar dianalisis secara kuantitatif. Pemerolehan hasil belajar dari nilai preetest pada pembelajaran I memperoleh rata-rata 67 dengan prosentase 51,90%, dan pembelajaran II memperoleh rata-rata 64 dengan prosentase 46,20%. Sedangkan, nilai hasil belajar posttest pada pembelajaran I memperoleh rata-rata 86 dengan prosentase 92,30%, dan pembelajaran II memperoleh rata-rata 88 dengan prosentase 92,30%. Berdasarkan data penelitian yang telah dilakukan dapat diketahui bahwa, media scrapbook dapat dijadikan sumber belajar yang tepat pada pembelajaran fiksi di sekolah dasar.